Development of a variable-profile cam to enhance the volumetric efficiency of IC engines - Sürmen, Ali; Arslan, Ridvan; Kopmaz, Osman; Avci, Atakan; Karagoz, Irfan; Karamangil, M. Ihsan (INDERSCIENCE ENTERPRISES LTD, 2017)
In this study, it is aimed to develop a new concept camshaft for continuously variable valve timing (CVVT). The concept is based on obtaining a curvilinear cam surface by integrating a number of conventional cam contours. Thirteen unworked camshafts, with arbitrary different contours, i. e., valve opening and closing times, were machined and tested on a fourstroke single-cylinder diesel engine to determine their volumetric efficiency at varied engine speeds. Then with suitable axial arrangement of these individual contours on a camshaft and integration of them, a single curvilinear cam surface was obtained. It is expected to get the same volumetric efficiency, with a ball contact follower when it follows a specific contour, as obtained when the specific cam of the same contour individually yielded. By giving an axial motion to the camshaft, allowing the follower to follow different contours, continuous variation of valve timing will be achieved.
Keywords: volumetric efficiency; variable valve timing; variable valve action; variable cam profile